Measuring the classroom level of the Dynamic Model of Educational Effectiveness through teacher self-report: development and validation of a new instrument - Dierendonck, Christophe (Frontiers in Education, 2023)
In the Dynamic Model of Educational Effectiveness (Creemers & Kyriakides, 2008), classroom-level effectiveness factors are assessed through observations or aggregated students' ratings. The current study is aimed at developing and validating a complementary teacher self-report instrument of effective practices at classroom level (the DMEE-Class-T). The new instrument showed concurrent validity with the CSS-T (Reddy et al., 2015). Dimensionality of both instruments was examined using the bifactor exploratory structural equation modeling (ESEM) framework, testing for alternative factorial representations of the data collected in a large-scale study conducted in all Luxembourgish elementary schools. For both instruments, the bifactor-ESEM and ESEM models showed excellent fitting indices and parameters, but the ESEM solution was retained as the best model for parsimony purpose. These results suggest that the eight types of practices assessed through the DMEE-Class-T could be considered as distinct facets of effective teaching practices while taking items crossloadings into account. Implications for research and teachers' professional development are discussed.